The influence of thermal reaction and microbial transformation on the odour of human urine1. (25th January 2013) - Troccaz, Myriam; Niclass, Yvan; Anziani, Pauline; Starkenmann, Christian; Natsch, Andreas
ABSTRACT The typical stale urine odour is the consequence of thermal or bacterial degradation. Gas chromatography–mass spectrometry, equipped with a multi‐sniffing port for olfactive evaluation (GC‐MS‐O), was performed to analyse an organic extract of boiled urine originating from seven male donors. This analysis stressed the importance of guaiacol, 2‐methoxy‐4‐ and ‐6‐methyl phenol, 4‐vinyl‐guaiacol, indole, skatole and vanillin in urine malodour. Analysis of the headspace of the highly volatile compounds showed the occurrence of trimethylamine, methyl mercaptan and dimethyl sulfide. However, odour artefacts such as pyrazines, acetyl thiazole and sugar degradation products were formed during the boiling process and represented important background noise. In parallel, fermented urine samples were judged by sniffing to be more characteristic of a urine smell, due to the presence of methional, phenol, p‐cresol and α‐androstenol. The two urine‐isolated Enterobacteriaceae, Escherichia fergusonii and Morganella morganii (urease positive), were particularly efficient at increasing urine pH and generating phenol, p‐cresol, indole, dimethyl sulfide and trimethylamine after 3 days of incubation of sterile male urine at 37 °C. Streptococcus agalactiae produced a high level of α‐androstenol, whereas Micrococcus luteus CIP 103664 and isolated anaerobic bacteria did not produce any malodours. Analytical comparisons between boiled and fermented aged urine revealed that incubation of sterile urine with a bacterial mixture of E. fergusonii, Enterococcus faecalis, Citrobacter koseri, S. agalactiae and M. morganii produced a representative aged urine odour. Copyright © 2013 John Wiley & Sons, Ltd.